Risk management in rainfed agriculture: An analysis of strategies and adaptations followed by farmers in Madhya Pradesh - J, RAGHAVENDRA K; SURESH, A (The Indian Journal of Agricultural Sciences, 2018)
Madhya Pradesh is the major producer of soybean in India. Being predominantly rainfed, the state faces high risks in its cultivation. The study undertook a primary survey in Madhya Pradesh to analyze the risk perception of farmers, elucidate the strategies followed by farmers to adapt with the risk and to identify the factors influencing their adoption. The results infer that late onset of monsoon, erratic rainfall and pest and diseases were the major risks. The major risks were related to untimely rainfall, drought and biotic factors like diseases and pest. The major adaptation strategies adopted were intercropping (49%), crop insurance (45%), micro irrigation (17%) and varietal diversification (39%). The study discerns need to develop drought tolerant varieties for rainfed regions, low cost micro-irrigation systems, enhanced credit availability to the farmers and promotion of crop insurance to adapt with production risks.